Growth Slowdown in Bureaucratic Economic Systems : An Issue Revisited - Bulir, Ales (IMF Working Papers; Working Paper ;, 2001)
Bureaucratically organized systems tend to be less efficient than economies in which agents are free to choose their output targets, as well as the means to meet them. This paper presents a simple model of planner-manager interactions and shows how bureaucratic economies can end up in a low-effort, low-growth equilibrium even though they may have started in high-effort , high-growth equilibrium. The empirical evidence from eight Central and Eastern European countries during 1948-49 is consistent with our model results, namely, that the growth decline was systemic in nature. The results are applicable to countries in other regions with heavy bureaucratic involvement in the economy.